Isolation and Identification of Endophytic Fungi from Syzygium cumini Linn and Investigation of Their Pharmacological Activities. (3rd November 2022) - Samapti, Mst. Mabiya Sultana; Afroz, Farhana; Rony, Satyajit Roy; Sharmin, Suriya; Moni, Fatema; Akhter, Shammi; Ahmed, Sheikh Feroz Uddin; Sohrab, Md. Hossain
Abstract : This study was conducted to isolate and identify the endophytic fungi from the bark and leaves of the Syzygum cumini plant and investigate the pharmacological activities of endophytic fungi along with plant parts. After isolation, endophytic fungi were identified based on morphological characteristics and molecular identification. Antimicrobial, antioxidant, and cytotoxic activities were studied by a disc diffusion method, free radical scavenging DPPH assay, and brine shrimp lethality bioassay, respectively. A total of eight endophytic fungi were isolated and identified up to the genus level based on morphological characteristics and confirmed by molecular identification techniques. Among the eight isolates, three isolates were identified as Colletotrichum sp. (SCBE-2, SCBE-7, and SCLE-9), while the rest of the isolates belonged to Diaporthe sp. (SCBE-1), Pestalotiopsis sp. (SCBE-3), Penicillium sp. (SCBE-4), Phyllosistica sp. (SCLE-7), and Fusarium sp. (SCLE-8). The presence of flavonoids, anthraquinones, coumarins, and isocoumarins was assumed by the preliminary screening of the fungal and plant extracts by a thin-layer chromatographic technique under UV light. Fungal extracts of Pestalotiopsis sp. Penicillium sp. were found sensitive to all test bacteria, but only extracts from the leaf and bark showed significant antifungal activity along with their antimicrobial activity. Penicillium sp. The fungal extract showed the highest free radical scavenging activity (2.43 μ g/mL) near that of ascorbic acid (2.42 μ g/mL). Some fungal extracts showed cytotoxic activity that, in general, suggests their probable abundance of biological metabolites. This is the first approach to investigate the endophytic fungi of Syzygium cumini Linn. in Bangladesh, to find the pharmacological potential of endophytes, and to explore novel compounds from those endophytes.